Tinjauan Hukum Tindak Pidana Perdagangan Orang Berdasarkan UU No. 21 Tahun 2007 dan Perma No. 1 Tahun 2022 tentang Restitusi - Prasetya Djati Nugraha; Nahdiya Sabrina (Postgraduate University of Merdeka Malang, 2026)
The crime of human trafficking is a serious violation of human dignity and requires comprehensive legal protection. Although the government has regulated it through Law No. 21 of 2007, the fulfillment of victims' rights, especially restitution, has not been effective. Therefore, the Supreme Court issued Regulation No. 1 of 2022 as a guideline for resolving restitution and compensation requests. This study examines the criminal provisions in Law No. 21 of 2007 and the legal implications of Regulation No. 1 of 2022 on the provision of restitution to victims, using normative legal research methods with statutory, conceptual, and case-based approaches. The results show that although Law No. 21 of 2007 provides a strong legal basis for eradicating human trafficking and protecting victims, its implementation remains hampered by procedural aspects and inter-agency coordination. Regulation No. 1 of 2022 strengthens victims' legal standing by clarifying perpetrators' responsibilities and enforcement mechanisms. However, the effectiveness of restitution remains limited due to the lack of sanctions or a state compensation scheme for perpetrators' inability to pay. Thus, the effectiveness of victim protection still needs to be strengthened through regulatory harmonization, institutional capacity building, and the application of restorative justice principles.